A simple interactive robot to promote computational thinking - Funk, Matthias; Cascalho, José; Santos, Ana Isabel; Pedro, Francisco; Medeiros, Paulo; Amaral, Bárbara; Domingos, Manuel; Ramos, Alberto; Mendes, Armando (Frontiers in Computer Science, 2022)
In this paper, we describe the functionalities of a simple robot to be adopted in the classroom to promote Computational Thinking (CT) in the context of the project PeCOT - Computational Thinking with Tangible Objects. This robot, similar to some commercial educational robots, was developed to be used in primary education classroom contexts (second, third and fourth grade) by children between 8 and 10 years old. PeCOT is a pedagogical intervention project and research project that will run over the next two years. The aim of this paper is to present the robot, how it works, and some activities that can be implemented in the educational context to promote CT skills, but also learning in different subject areas, such as mathematics or natural science. Thus, we begin by presenting a general description of the robot. Next, we identify activities and formalize the programming steps for each of the activities. Finally, we discuss the potential that the robot and the proposed activities may have to promote CT skills development.